Cervical Preparation Using Ulipristal Acetate With Adjunct Misoprostol in Second-Trimester Surgical Abortions. Issue 5 (5th May 2022) - Peterson, Sarah F.; Lerma, Klaira; Shaw, Kate A.; Blumenthal, Paul D.
Abstract : Ulipristal acetate could serve as an alternative method of cervical preparation before second-trimester abortion procedures, thereby aiding clinicians in providing timely abortion care.